Can resistant Helicobacter pylori infection be estimated histologically: Effects of gastric histology on eradication rates of Helicobacter pylori infection - Vildan TAŞKIN,; Esin ÖZYILKAN,; Abdullah AYDIN,; Faruk ÇETİN,; Erdal ESKİOĞLU,; Tankut KÖSEOĞLU, (Turkish Journal of Gastroenterology, 2019)
-